A participatory and capacity-building approach to healthy eating and physical activity - SCIP-school: a 2-year controlled trial - Elinder Liselotte Schäfer; Heinemans Nelleke; Hagberg Jan; Quetel Anna-Karin; Hagströmer Maria (BMC, 2012)
Abstract Background Schools can be effective settings for improving eating habits and physical activity, whereas it is more difficult to prevent obesity. A key challenge is the "implementation gap". Trade-off must be made between expert-driven programmes on the one hand and contextual relevance, flexibility, participation and capacity building on the other. The aim of the Stockholm County Implementation Programme was to improve eating habits, physical activity, self-esteem, and promote a healthy body weight in children aged 6-16 years. We describe the programme, intervention fidelity, impacts and outcomes after two years of intervention. Methods Nine out of 18 schools in a middle-class municipality in Sweden agreed to participate whereas the other nine schools served as the comparison group (quasi-experimental study). Tailored action plans were developed by school health teams on the basis of a self-assessment questionnaire called KEY assessing strengths and weaknesses of each school's health practices and environments. Process evaluation was carried out by the research staff. Impacts at school level were assessed yearly by the KEY. Outcome measures at student level were anthropometry (measured), and health behaviours assessed by a questionnaire, at baseline and after 2 years. All children in grade 2, 4 and 7 were invited to participate (n=1359) of which 59.8% consented. The effect of the intervention on health behaviours, self-esteem, weight status and BMIsds was evaluated by unilevel and multilevel regression analysis adjusted for gender and baseline values. Results Programme fidelity was high demonstrating feasibility, but fidelity to school action plans was only 48% after two years. Positive and significant (p<.05) impacts were noted in school health practices and environments after 2 years. At student level no significant intervention effects were seen for the main outcomes. Conclusions School staff has the capacity to create their own solutions and make changes at school level on the basis of self-assessment and facilitation by external agents. However these changes were challenging to sustain over time and had little impact on student behaviours or weight status. Better student outcomes could probably be attained by a more focused and evidence-based approach with stepwise implementation of action plans.